Diagnostic yield of ambulatory EEGs in the elderly. Issue 7 (July 2017) - Tolchin, Benjamin; Lee, Jong Woo; Pavlova, Milena; Dworetzky, Barbara A.; Sarkis, Rani A.
Highlights: 37% of studies reveal diagnostic findings and 21% result in change in management. Focal slowing on routine EEG predicts epileptiform abnormalities on ambulatory EEG. Ambulatory EEG duration correlates with capture of typical nonepileptic events. Abstract: Objective: The diagnostic yield of ambulatory EEG in the elderly is not known. We sought to determine diagnostic yield and identify factors predicting diagnostic findings in this elderly population. Methods: We reviewed 156 consecutive 24–72 h ambulatory EEGs performed on patients aged 60 or older. Results: Of the 156 studies, 58 studies (37%) revealed potentially diagnostic findings: either epileptiform discharges, an epileptic seizure, or a typical nonepileptic event. Focal slowing on routine EEG predicted epileptiform abnormalities on ambulatory EEG with an odds ratio of 4.0 (95% CI 1.7–9.7, p  = 0.002). Age, the presence of a focal lesion on MRI, and duration of ambulatory EEG failed to predict epileptiform abnormalities on ambulatory EEG. Duration of ambulatory EEG predicted capture of a typical nonepileptic event with an odds ratio of 2.7 (95% CI 1.3–5.7, p  = 0.009) for every additional day of study duration. Conclusions: Focal slowing on routine EEGs may warrant an ambulatory EEG in the setting of diagnostic uncertainty. Longer ambulatory EEGs have a higher yield in capturing patients' typical non-epileptic events, and should be considered in patients where nonepileptic events are a likely diagnostic possibility. Significance: These findings offer guidance in the use of ambulatory EEGs in the elderly.